Small ruminant productivity and nutrition in southern Nigeria - Reynolds, L.; Adeoye, S.A.O. (1985)
An experiment was carried out over 2 years period to investigate effect of levels of browse supplementary offered to West African Dwarf (Djallonke) sheep on productivity. The results of this on-station trail showed that overall lambing interval was 239 days (ranging from 262 days to 226 days).Birth weight of lambs was 1.68 kg while dams weight before birth was 25.5 kg. Overall litter size was 1.28±0.041. On average survival to 90 days was 0.65 with daily live weight gain being 70.5g. The cumulative effect of these factors resulted in overall 9.72 kg of kids per dam survival to 90 days per year. In addition data on these parameters were recorded under different levels of supplementation to evaluate effect of dietary regime on productivity.